Challenges in the Initial Stage of Institutional Repository Implementation: A Study of Malaysian Public Universities - Saad, Nor Hasliza Md (2017)
Knowledge management has been received the widespread attention from higher education institutions in their practice of managing institutional repository. With the significant growth in the need for managing and sharing information across different departments, the need for managing digital repository is felt more than ever. An institutional repository may include a wide range of digital contents such as journal articles, conference papers, book chapters, monographs, research reports, theses, patent, presentations, audio material and multimedia materials. The purpose of this research is to investigate the implementation of institutional repositories practice in Malaysian public universities. This paper presents the initial findings from electronic survey conducted at Malaysian public universities. Recently, many Malaysian public universities are now have built their institutional repositories, while some considering or working towards implementing them. There is no doubt academic library has its new challenge in managing its institutional repository not only from technological aspect but also management support and librarian skills. The conventional role of academic library is changing to meet new requirement of skills in information science and information technology in supporting knowledge management approach. It is prime concern for any academic library to understand the current challenge of managing institutional repository and to identify the prime supporting activities for its librarian to better serve the needs of academic community.